Fabrication and Characterization of Chitosan/Poly(Lactic-Co-glycolic Acid) Core-Shell Nanoparticles by Coaxial Electrospray Technology for Dual Delivery of Natamycin and Clotrimazole - Cui, Xiaoming; Li, Xiaoli; Xu, Zhilu; Guan, Xiuwen; Ma, Jinlong; Ding, Dejun; Zhang, Weifen (Frontiers in Bioengineering and Biotechnology, 2021)
Natamycin (NAT) is the drug of choice for anti-fungal keratitis (FK), but it also has some unsatisfactory factors such as poor solubility, high dosing frequency and long treatment cycle, which usually requires adjuvant therapy with other drugs. Therefore, a new dosage form of NAT urgently needs to be designed for the treatment of FK. Clotrimazole (CLZ) is a broad spectrum anti-fungal agent and growing research confirms that it plays a significant role in fungal growth inhibition. In our study, the nanosystem is consisted of NAT and CLZ co-delivered by chitosan and poly (lactic-co-glycolic acid) and prepared by coaxial electrospray (CO-ES) technology to enhance the treatment effect, shorten cycle for FK treatment. The characteristic results showed that formulations had obvious core-shell structure and uniform particle distribution. The NAT/CLZ@CTS/PLGA NPs have high encapsulation efficiency (NAT, 85.63 ± 0.04%; CLZ 89.61 ± 0.04%) and drug loading capacity (NAT, 6.65 ± 0.01%; CLZ, 1.39 ± 0.01%), with a nano hydrodynamic diameter (309-406 nm). NAT and CLZ were found to sustain release over 36 h in vitro. Furthermore, good biosafety and significant anti-candidiasis effect were also found in the NAT/CLZ@CTS/PLGA NPs. Therefore, this design may provide a promising drug delivery system and new option for the treatment of FK.